Analysis of Risk Factors for Development of Hepatocellular Carcinoma in Chronic HBV - Infected Liver Cirrhosis Patients: A Meta-Analysis - Xiang Lyu; Gaofeng Cai; Kui Liu; Sichao Huang; Jun Yao; Zhenggang Jiang; Zhengting Wang; Zhifang Wang; Yongdi Chen; Huakun Lv; Jianmin Jiang (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2017)
The 5-year cumulative incidence rate of hepatocellular carcinoma (HCC) in chronic HBV -infected liver cirrhosis (LC) patients was up to 5%-30%. However, existing medical interventions can't cure chronic HBV -infected LC patient. At present, the association between risk factors and development of chronic HBV -infected HCC have been explored by previous studies, but the results remains inconsistent. We took the chronic HBV -infected LC patients as the research object. We systematically searched for studies evaluating whether those proposed factors changed HCC risk from Chinese Medical Journal Database, Chinese National Knowledge Infrastructure, Pubmed, Elsevier, Springer, Wiley, OVID, EBSCO in BoKu data service platform. Odds ratios (OR) with 95% confi dence intervals (CI) were calculated by Review Manager 5.0. In this meta-analysis, 1088 cases and 602 controls from 6 studies were included. Our results showed that pooled OR with 95% CI for the factors analyzed were: non-antiviral treatment 3.59(2.73, 4.72), high HBV DNA levels 3.12(2.29, 4.25), drinking alcohol 1.86(1.41, 2.26), a family history of HCC 10.12(4.23,24.25), male gender 1.48(1.13, 1.95), smoking 2.93(1.99, 4.40), a history of diabetes mellitus 5.87(3.06, 11.27), a family history of HBV 1.20(0.92,1.57), a history of fatty liver 2.29(1.22,4.32) and HBeAg positive 2.05(1.15, 3.68), respectively. Non-antiviral treatment, high HBV DNA levels, drinking alcohol, smoking,a family history of HCC, male gender, a history of diabetes mellitus, a history of fatty liver and HBeAg positive can increase the development risk of HCC in chronic HBV -infected LC patients from currently available evidence.